Pelatihan Pemilihan Lembaga Keuangan Yang Tepat Untuk Kebutuhan Rumah Tangga - Siti Nurcahayati; Ayu Puspa Lestiyadi; Ratna Dumilah (PT. Karya Inovatif Nusantara, 2026)
The target group for this activity is women attending religious study groups, who play a crucial role in household financial management. Based on initial observations, it was found that most participants still lacked an understanding of the various types of financial institutions and were unable to select one that best suited their household needs. Furthermore, their understanding of financial products such as savings, credit, insurance, and investments was also limited. This situation has the potential to lead to errors in financial decision-making and even increase the risk of becoming trapped in illegal financial institutions. To address these issues, the PKM team offered a solution through training activities. The implementation methods included counseling, training, discussions, and financial decision-making simulations. The material presented included an introduction to formal and informal financial institutions, how to choose a trustworthy financial institution, and effective household financial management strategies. With this approach, it is hoped that participants will not only understand the theory but also be able to apply it in their daily lives. The expected outcomes of this activity are increased financial literacy among women attending religious study groups, the ability to choose the right financial institution, and the creation of wiser and more planned household financial management. Thus, this activity is expected to have a positive impact on family economic well-being and reduce the risk of financial problems in the community.